Cost Analysis and Determinants of Inefficiency of Hemodialysis Services - Dwi Suwondo; Evi Octavia (Journal of Social Research, 2025)
This study aims to analyze the cost of hemodialysis services in patients with Chronic Kidney Failure (CKD) at Dr. Abdul Radjak Purwakarta Hospital using the Activity-Based Costing (ABC) approach with a bottom-up method. In addition, this study also identifies inefficiency factors through Value Stream Mapping (VSM) analysis. This study is quantitative descriptive research that aims to determine the value of independent variables, either one or more variables, without making comparisons with other variables. The results of the study showed that the cost of hemodialysis units amounted to Rp 949,048 per action, consisting of direct costs of Rp 752,513, direct resources overhead of Rp 131,498, and indirect resources overhead of Rp 65,037. The largest cost component comes from the labour-related aspect, accounting for 62.7% of the total direct costs, followed by service-related (24.2%) and non-functional unit employee costs (75.72% of indirect overhead). The efficiency of the service process reached 92%, but it was found that 8% of non-value added activities mainly occurred in the registration and final administration process. A comparison between ABC's unit cost and INA-CBG's rate shows a cost difference, with a cost recovery rate of 99%, which means hospitals have a deficit of 1% per procedure. The results of this study confirm the importance of using the ABC method in the calculation of hospital service costs as well as the integration of lean approaches to improve operational efficiency and accuracy of financial decision-making in the hemodialysis service unit.